Drip-and-ship versus mothership for endovascular treatment of acute stroke: A comparative effectiveness analysis. Issue 3 (March 2022) - Wu, Xiao; Wira, Charles R; Matouk, Charles C; Forman, Howard P.; Gandhi, Dheeraj; Sanelli, Pina; Schindler, Joseph; Malhotra, Ajay
Background: Triage for suspected acute stroke has two main options: (1) transport to the closest primary stroke center (PSC) and then to the nearest comprehensive stroke center (CSC) (Drip-and-Ship) or (2) transport the patient to the nearest CSC, bypassing a closer PSC (mothership). The purpose was to evaluate the effectiveness of drip-and-ship versus mothership models for acute stroke patients. Methods: A Markov decision-analytic model was constructed. All model parameters were derived from recent medical literature. Our target population was adult patient with sudden onset of acute stroke within 8 h of onset over a one-year horizon. The primary outcome was quantified in terms of quality-adjusted-life-years (QALYs). Results: The base case scenario show that the drip-and-ship strategy has a slightly higher expected health benefit, 0.591 QALY, as compared to 0.586 QALY in the mothership strategy when the time to PSC is 30 min and to CSC is 65 min, although the difference in health benefit becomes minimal as the time to PSC increases towards 60 min. Multiple sensitivity analyses show that when both PSC and CSC are far from place of onset (>1.5 h away), drip-and-ship becomes the better strategy. Mothership strategy is favored by smaller difference between distances to PSC and CSC, shorter transfer time from PSC to CSC, and longer delay in reperfusion in CSC for transferred patients. Drip-and-ship is favored by the reverse. Conclusion: Drip-and-ship has a slightly higher utility than mothership. This study assesses the complex issue of prehospital triage of acute stroke patients and can provide a framework for real-world data input.